The serious human rights crisis in Brazil and its implications for indigenous peoples: In search of favorable legal criteria from the Latin American experience - Corrêa de Almeida, Marina (2020)
The present article is part of the result of postdoctoral research work that seeks to find, in international and Latin American jurisprudence, favorable criteria for agreements that guarantee respect for the multiethnic and multicultural condition of our nations and, in this way, the human rights of indigenous peoples of the region.  In this sense, the proposed analysis pursues to find possibilities to contribute to the development of Brazilian jurisprudence on the subject matter, considering that Brazilian indigenous peoples are currently facing a new period of dispossession and violence towards their community forms of life in their territories.  We employ the socio-historical analysis of the current situation in the field of struggle that is the discourse of human rights in Brazil, and its effectiveness for the defense of the collective rights of indigenous peoples, especially their right to territory and natural resources.  Then, we move on to the exercise of jurisprudential analysis, to the standards of the Inter-American Court of Human Rights on the subject, in order to find in them favorable meanings to the protection of the collective rights of peoples.  Thus, the present work finds in these legal discourses criteria that can be recommended to the Supreme Court of Brazil, as legitimate approaches for the respect and protection, of both the collective right to territory and natural resources that indigenous peoples have in accordance with international and Inter-American law, and as grounds to affirm the importance of consultation to guarantee the right to self-determination of peoples.